Myricetin Potentiates Antibiotics Against Resistant Pseudomonas aeruginosa by Disrupting Biofilm Formation and Inhibiting Motility Through FimX-Mediated c-di-GMP Signaling Interference - Derong Zeng; Fangfang Jiao; Yuqi Yang; Shuai Dou; Jiahua Yu; Xiang Yu; Yongqiang Zhou; Juan Xue; Xue Li; Hongliang Duan; Yan Zhang; Jingjing Guo; et al. (Biology)
Pseudomonas aeruginosa biofilm formation is critical to antibiotic resistance and persistence. Targeting cyclic di-GMP (c-di-GMP) signaling, a master biofilm formation and virulence regulator, presents a promising strategy to combat resistant bacterial infections. Myricetin, a natural polyphenolic flavonoid with documented antimicrobial and anti-biofilm activities, may enhance antibiotic efficacy against Pseudomonas aeruginosa. This study evaluated the synergistic effects of myricetin combined with azithromycin, ciprofloxacin, or cefdinir against both standard and drug-resistant Pseudomonas aeruginosa strains. Antibacterial activity, biofilm disruption, and motility inhibition were experimentally assessed, while molecular dynamic (MD) simulations elucidated myricetin’s molecular mechanism of action. Our results suggested that myricetin synergistically potentiated all three antibiotics, reducing c-di-GMP synthesis by 28% (azithromycin), 57% (ciprofloxacin), and 30% (cefdinir). It enhanced bactericidal effects, suppressed biofilm formation, and impaired swimming, swarming, and twitching motility. Computational analyses revealed that myricetin binds allosterically to FimX very well, a key regulator in the c-di-GMP signaling pathway. Hence, myricetin may act as a c-di-GMP inhibitor, reversing biofilm-mediated resistance in Pseudomonas aeruginosa and augmenting antibiotic efficacy. This integrated experimental and computational approach provides a framework for developing anti-virulence and antibiotic combination therapies against recalcitrant Gram-negative pathogens.